Digital Ecosystem for Rice Activity Monitoring and Reporting (RiceMoRe) - Yen, Bui Tan (International Rice Research Institute, 2024)
Rice Activity Monitoring and Reporting System (RiceMoRe) is a comprehensive digital solution developed through the collaboration of the Department of Crop Production (DCP), the Center for Agriculture Digital Transformation and Statistics (DTS), the International Rice Research Institute (IRRI), and TCSOFT. Designed to support the monitoring and reporting of rice production activities, RiceMoRe aims to enhance the efficiency, accuracy, transparency, traceability, and accessibility of agricultural data across Vietnam. Since its initiation in 2018, the system has undergone continuous development and is set to be evaluated, finalized, and officially transferred to the Ministry of Agriculture and Rural Development (MARD) for national management in 2024. Key functions of RiceMoRe include standardizing rice activity data from the communal to the national level, supporting geo-referenced data collection, recording near-real-time production activities, enabling data querying, synchronization, and extraction, and managing hierarchical user accounts. Looking ahead, RiceMoRe holds significant potential for expanding Vietnam’s digital agricultural ecosystem. This includes integrating large-scale geo-referenced data with other data sources, extending its application to over 30 other crop products, and scaling out to diverse agro-ecological regions. The system represents a transformative step toward data-driven agricultural management and sustainable rice production in Vietnam.